2017
DOI: 10.5152/turkjorthod.2017.17019
|View full text |Cite
|
Sign up to set email alerts
|

Dental Arch Dimensions of Nigerian Children with Hypertrophied Adenoids

Abstract: Objective: The study objective was to assess the effect of adenoid hypertrophy on the dental arch dimensions of children in Ile-Ife, Nigeria.Methods: Ninety patients aged 3-12 years attending the Otorhinolaryngology Clinic at Obafemi Awolowo University Teaching Hospital Ile-Ife diagnosed as having hypertrophied adenoids and 90 children from the Child Dental Health Clinic were recruited as adenoid and control subjects respectively. Arch and palatal vault dimensions, including total arch length; inter-canine, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The results of this study showed that the N-Me, ANS-Me, N-Me/S-Go, and ANS-Me/N-Me values were higher in the observation group than in the control group, and the Go-Gn values were lower than in the control group, indicating increased mandibular steepness in children with adenoid hypertrophy. The reasons for this are that adenoid hypertrophy causes airway obstruction and narrowing of the upper airway in children, and at this time, the lower jaw needs to be extended forward to keep the airway open, plus open-mouth breathing causes the child's lower jaw to rotate back clockwise, increasing the steepness of the lower jaw and contributing to excessive vertical growth and development of the lower jaw, resulting in an elongated face and increased N-Me and ANS-Me [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the N-Me, ANS-Me, N-Me/S-Go, and ANS-Me/N-Me values were higher in the observation group than in the control group, and the Go-Gn values were lower than in the control group, indicating increased mandibular steepness in children with adenoid hypertrophy. The reasons for this are that adenoid hypertrophy causes airway obstruction and narrowing of the upper airway in children, and at this time, the lower jaw needs to be extended forward to keep the airway open, plus open-mouth breathing causes the child's lower jaw to rotate back clockwise, increasing the steepness of the lower jaw and contributing to excessive vertical growth and development of the lower jaw, resulting in an elongated face and increased N-Me and ANS-Me [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maxillofacial morphological changes occur because mouth breathing results in adaptive changes in the lips, tongue, and mandible, which further impact the skeletal alterations by neuromuscular responses. The traditional view is that children with mouth breathing often present with a skeletal Class II facial profile characterized as maxillary protrusion and mandibular retrusion ( 41 , 42 ), along with the clockwise rotation of the mandible ( 28 , 43 ), an increase in lower anterior height ( 44 , 45 ), protruding upper lip ( 46 ), incompetent lip seal ( 47 ), nasal flaring and high palatal vault ( 48 , 49 ). A systematic review of 19 studies compared cephalometric data in children and adolescents with oral and nasal breathing.…”
Section: The Impact Of Mouth Breathing On Maxillofacial Developmentmentioning
confidence: 99%
“…29 Anak yang bernapas melalui mulut cenderung memiliki lengkung rahang atas berbentuk V yang sempit dan palatum yang tinggi. Penelitian oleh Kusumaningrum et al, 30 Acharya et al, 28 Molina et al, 5 Chambi-Rocha et al, 31 Indiarti et al, 32 dan Ijeoma et al, 33 menunjukkan hasil yang sama, yaitu mouth breathing memengaruhi dimensi vertikal palatum anak yang mengalaminya yaitu memiliki kedalaman palatum yang tinggi. Mouth breathing menginduksi perubahan morfologi pada palatum durum karena tidak ada tekanan negatif di rongga hidung yang mencegah penurunan palatum dan kerja tulang wajah serta otot lain yang membantu dalam menekan lengkung rahang atas bagian luar, sehingga pertumbuhan lebih menonjol secara vertikal.…”
Section: Pembahasanunclassified
“…Acharya et al 28 dan Ijeoma et al 33 dalam penelitiannya juga menemukan perubahan palatum dalam arah transversal, jika lebar lengkung rahang atas pendek sehingga palatum menjadi sempit khususnya terjadi para daerah posterior di regio premolar hingga molar. Bila postur lidah normal, lidah bertumpu pada palatum durum.…”
Section: Pembahasanunclassified